THE PEDAGOGICAL COMPETENCE OF TEACHERS OF AL-QUR’AN HADITH STUDIES IN THE IMPLEMENTATION OF THE 2013 CURRICULUM - Nurmiati, Nurmiati (Idaarah: Jurnal Manajemen Pendidikan, 2021)
Abstract: The Pedagogical Competence of Teachers of al-Qur'an Hadith Studies in the Implementation of the 2013 Curriculum The focus of this research is the pedagogical competence of teachers of al-Qur'an Hadith in the implementation of the 2013 curriculum. This research is a qualitative descriptive using a pedagogical and socio-cultural approach with data triangulation methods. The primary data consisted of the Head of Madrasah, teachers of al-Qur'an Hadith studies, and deputy head of madrasah for curriculum, public relations, student affairs, and facilities and infrastructure. Secondary data is in the form of documentation from teachers of al-Qur'an Hadith, educational staff, books, journals, and other supporting data. Data were collected through observation, interviews, and documentation.The results of this research show that teachers of al-Qur'an Hadith have the competence of pedagogy in implementing the 2013 curriculum, but in its implementation, there are still deficiencies especially in terms of making learning tools, which is not optimal, because there are still teachers who copy and paste the learning tools from the internet as well as in terms of the limitations of teachers of al-Qur'an Hadith in the use of learning media so that they cannot be utilized by the students. This research is expected to create synergy between government programs with all parties involved in implementing the al-Quran Hadith curriculum, especially at the Madrasah level in Makassar to improve the pedagogical competence of teachers of al-Qur'an Hadith and become solutions as well as the motivation of students in improving the quality of learning so that students can actualize the materials learned in everyday life to achieve the goals of Islamic Education. Keywords: Competence, Teacher of al-Qur’an Hadith, Curriculum, Islamic Education. Abstrak: Kompetensi Pedagogi Guru Bidang Studi al=Qur’an Hadist dalam Penerapan Kurikulum 2013 Fokus penelitian adalah kompetensi guru bidang studi al-Qur’an Hadis dalam pelaksanaan kurikulum 2013, Penelitian ini menggunakan penelitian deskriptif kualitatif dengan mengggunakan pendekatan pedagogi dan sosio-kultural dengan metode triangulasi data, Lokasi penelitian di Madrasah Ibtidaiyah Negeri 2 Makassar. Sumber datanya primer dan sekunder. Data primer berupa informan kepala madrasah, guru bidang studi al-Qur’an Hadis dan wakil kepala madrasah bagian kurikulum, humas, kesiswaan, dan sarana dan prasarana. Data sekunder berupa dokumentasi dari guru bidang studi al-Qur’an Hadis, tenaga kependidikan, buku, jurnal, dan data pendukung lainnya. Data dikumpulkan dengan metode observasi, wawancara dan dokumentasi. Instrumen penelitian yaitu peneliti sendiri dengan menggunakan sarana penggalian data. Teknik pengolahan data melalui empat tahapan yaitu, reduksi data, penyajian data, penarikan kesimpulan dan verifikasi data. Hasil penilitian menunjukkan bahwa guru bidang studi al-Qur’an hadis memiliki kompetensi fedagogi dalam penerapan kurikulum 2013, namun dalam pelaksanaannya masih terdapat kekurangan terutama dalam hal membuat perangkat pembelajaran belum optimal, oleh karena masih ada guru bukan menjadikan internet sebagai bahan rujukan akan tetapi meng-copy paste perangkat pembelajarannya dari internet begitupun dalam hal keterbatasan guru bidang studi al-Qur’an Hadis dalam penggunaan media pembelajaran, sehingga belum bisa dinikmati oleh semua peserta didik. Penelitian ini diharapkan terwujudnya sinergi antara program pemerintah dengan semua pihak yang terlibat dalam pelaksanaan kurikulum bidang studi al-Quran hadis, khususnya pada jenjang Madrasah Ibtidaiyah di Kota Makassar dan dapat meningkatkan kompetensi guru bidang studi al-Qur’an hadis, serta menjadi solusi sekaligus motivasi peserta didik dalam peningkatan kualitas belajar seiring dengan pesatnya perkembangan zaman, sehingga peserta didik mampu mengaktualisasikan materi-materi yang dipelajari dalam kehidupan sehari-hari untuk mencapai tujuan pendidikan islam. Kata Kunci: Kompetensi, Guru bidang studi al-Qur’an Hadis, Kurikulum, Pendidikan Islam